Pengaruh Terapi Okupasi Berkebun terhadap Penurunan Depresi Lansia: Studi Quasi Eksperimen: The Effect of Gardening-Based Occupational Therapy on Reducing Depression in the Elderly: A Quasi-Experimental Study - Juwariah, Titik; Setiyorini, Erni (Chakra Brahmanda Lentera Institute, 2026)
Indonesia is currently entering a phase of population aging, with an increasing proportion of elderly people. Elderly individuals are more susceptible to psychosocial issues such as stress, loneliness, low self-esteem, and anxiety. This condition is exacerbated by a lack of physical activity, making them susceptible to health problems such as joint pain, degenerative diseases, and cognitive decline. These various issues increase the risk of depression in the elderly. Gardening occupational therapy is a non-pharmacological therapy that can be applied to elderly people with depression. The purpose of this study was to determine the effect of gardening occupational therapy on reducing depression in the elderly. The study design was a quasi-experimental study with a pre-posttest without a control group. A sample of 20 elderly individuals was selected using a purposive sampling technique. The inclusion criteria were: no cognitive impairment, able to understand simple instructions, depression, no serious illness, and no severe physical mobility impairment. The study was conducted over a one-month period in Singonegaran Village, Kediri. The research instrument used was the Geriatric Depression Scale-15 (GDS-15). The results showed that gardening occupational therapy significantly reduced depression in the elderly, as indicated by a change in scores from an average of 9 to 4.3, with a p-value of 0.003. Gardening therapy, as an occupational intervention, provides simultaneous physical, social, and cognitive stimulation that plays a role in reducing depressive symptoms by increasing daily activity, social interaction, and a sense of personal accomplishment as participants engage in caring for and witnessing plant growth.